Power, control and organisational learning - Normand Filion; Hedwig Rudolph (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
A review of managerial literature highlights the crucial importance of shared culture and common schemes of interpretation in organisational learning. The interpretative and sensemaking approaches of organisational learning insert themselves deeply in the process of the construction of social uniformity and cognitive homogeneity. Individual learning, culture, beliefs and rationality - the shared mental models - are the targets of confirmation processes. Thus, this specific kind of organisational learning cannot be considered as normatively neutral, but as a political process. A case study of a bank illustrates that organisational learning can be based on a structured social construction of cognitive homogeneity which generates an increase of control and enhances power of the management by reinforcing the legitimacy of decisions. However, this case study also shows that learning and non-learning are the two faces of the same process or, in other words, that organisational learning can produce unawareness and unintentional nonlearning by too much cultural uniformity. – – Eine Durchsicht der Managementliteratur verdeutlicht die zentrale Bedeutung gemeinsamer Kultur und geteilter Deutungsmuster für das Organisationslernen. Die interpretativen und deutungsbezogenen Ansätze des Organisationslernens basieren auf tiefgreifenden Prozessen zur Konstruktion sozialer Einheitlichkeit und kognitiver Homogenität. Die Absicherungsprozesse beziehen sich auf das individuelle Lernen, Kultur, Werthaltungen und Rationalität - die gemeinsamen mentalen Modelle. Insofern kann diese Form des Organisationslernens nicht als wertneutral angesehen werden; es handelt sich vielmehr um einen politischen Prozeß. An einer Fallstudie in einer Bank wird illustriert, daß Organisationslernen auf einer sozial konstruierten kognitiven Homogenität aufgebaut werden kann. Dabei wird Management-Kontrolle erweitert und ihre Macht verstärkt, indem die Legitimität ihrer Entscheidungen abgesichert wird. Allerdings dokumentiert die Fallstudie auch, daß Lernen und Nicht-Lernen zwei Seiten des gleichen Prozesses sind, anders gewendet: Organisationslernen kann zur Ausblendung von Wahrnehmung beitragen und - unbeabsichtigt - Nicht-Lernen generieren, wenn zuvor ein zu hohes Maß an kultureller Homogenität etabliert worden ist.
Keywords: 330